A landscape of Digital Humanities in Italy: backgrounds, institutions and infrastructures - Ciotti, Fabio (Testo e Senso, 2016)
This paper gives an overall diachronic and synchronic sketch of the situation in the Italian digital scholarship in the humanities and cultural heritage and advocates the relevance of research infrastructural initiatives to facilitate its future development. The recent establishment of Digital Research Infrastructure for the Arts and Humanities (DARIAH) as a formal European research infrastructure, and the Italian participation in it, have to be seen as a substantial step forward in this context. After a brief introduction to DARIAH structure and objectives, the paper identifies some fundamental actions and assets it can offer to foster the development of Digital Humanities research.